2019
DOI: 10.1002/eap.2011
|View full text |Cite
|
Sign up to set email alerts
|

Setting priorities for conservation at the interface between ocean circulation, connectivity, and population dynamics

Abstract: Population persistence in the marine environment is driven by patterns of ocean circulation, larval dispersal, ecological interactions, and demographic rates. For habitat‐forming organisms in particular, understanding the relationship between larval connectivity and meta‐population dynamics aids in planning for marine spatial management. Here, we estimate networks of connectivity between fringing coral reefs in the northwest shelf of Australia by combining a particle tracking model based on shelf circulation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…Although the region has experienced levels of heat stress typically associated with coral bleaching and mortality [47,82], these effects may have been mediated by local factors in the Dampier Archipelago, resulting in unexpected distribution patterns. Environmental factors not investigated in this study, including substrate type, nutrient influx and hydrodynamic patterns, may have influenced the distribution of species and resilience of coral reefs in the Dampier Archipelago [100,101].…”
Section: Discussionmentioning
confidence: 99%
“…Although the region has experienced levels of heat stress typically associated with coral bleaching and mortality [47,82], these effects may have been mediated by local factors in the Dampier Archipelago, resulting in unexpected distribution patterns. Environmental factors not investigated in this study, including substrate type, nutrient influx and hydrodynamic patterns, may have influenced the distribution of species and resilience of coral reefs in the Dampier Archipelago [100,101].…”
Section: Discussionmentioning
confidence: 99%
“…Because areas of high and low seasonal and interannual SST variability exist in the western Pilbara, and to coincide with patterns of bleaching in the period between 2011 and 2016, it may be possible to optimise future management strategies by understanding how these patterns may affect the overall system resilience. For example, spatio-temporal refugia provided by such variability, which appears to be greater than that on Australia's other tropical coasts, may interact with ecosystem properties such as regional connectivity to affect resilience (Boschetti et al 2017). An understanding of connectivity regimes among coral populations within the region is emerging on the basis of both hydrodynamic modelling (Feng et al 2016;Boschetti et al 2017) and genetic studies.…”
Section: Discussionmentioning
confidence: 99%
“…For example, spatio-temporal refugia provided by such variability, which appears to be greater than that on Australia's other tropical coasts, may interact with ecosystem properties such as regional connectivity to affect resilience (Boschetti et al 2017). An understanding of connectivity regimes among coral populations within the region is emerging on the basis of both hydrodynamic modelling (Feng et al 2016;Boschetti et al 2017) and genetic studies. Particle-track modelling shows that reefs to the north of Barrow Island have a low connectivity with those to the south (Feng et al 2016), which was corroborated in a recent coral population-genetic study of Cyphastrea microphthalma, which showed low levels of differentiation among some Pilbara reefs (Evans et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This inference is supported by hydrodynamic particle dispersion modelling, which shows that Ningaloo probably receives larvae from the reefs farther north (Feng et al 2016). Furthermore, the amount of larvae that are transported to Ningaloo varies from year to year, and supply varies among individual reefs, such that recovery times of many reefs are likely to be decades or longer (Boschetti et al 2019).…”
Section: )mentioning
confidence: 83%
“…The faster rates of warming yielded by downscaled models and evidence from coral cores mean that this might occur sooner. Exacerbating the likely increase in the frequency of bleaching is the potential for reduced supply of larvae from weaker currents, because the coral reefs to the north are likely to be sources of larvae for Ningaloo (Boschetti et al 2019), and coral abundance on these reefs has already been significantly reduced (Gilmour et al 2019.…”
Section: The Future Of Ningaloomentioning
confidence: 99%